Attack Rate for Wild-Type SARS-CoV-2 during Air Travel: Results from 46 Flights Traced by German Health Authorities, January–March and June–August 2020 - Felix Moek; Anna Rohde; Meike Schöll; Juliane Seidel; Jonathan H. J. Baum; Maria an der Heiden (Canadian Journal of Infectious Diseases and Medical Microbiology)
Background. Evidence on the risk of SARS-CoV-2 transmission during air travel is scarce. We aimed to estimate the attack rate for wild-type SARS-CoV-2 to improve the evidence base for the adaptation of nonpharmaceutical intervention (NPI) strategies aboard airplanes. Methods. In collaboration with German Public Health Authorities (PHA), we conducted a follow-up of in-flight SARS-CoV-2 contact persons. We included those contact persons whom the Emergency Operations Centre at the Robert Koch-Institute had forwarded to PHA between January to March 2020 (before masking on flights became mandatory) and June to August 2020 (after the introduction of mandatory masking). We retrospectively collected data on whether these contact persons had been successfully contacted, had become symptomatic and had been tested for SARS-CoV-2, and whether alternative exposures other than the flight were known. Results. Complete data that allowed for the calculation of attack rates were available for 108 contact persons (median age of 36 (IQR 24–53), 40% female), traveling on 46 flights with a median flight duration of 3 hours (IQR 2–3.5). 62 of these persons travelled after masking on flights became mandatory. 13/87 developed symptoms, 44/77 were tested (no data for 21 and 31). 13 persons (9 of whom had been SARS-CoV-2 positive) were excluded from the analysis of attack rates due to a likely alternative exposure. We thus identified 4 probable in-flight transmissions (2 of which occurred after the introduction of mandatory masking). The overall attack rate resulted in 4.2% (4/95; 95% CI: 1.4%–11.0%). Considering flights after mandatory masking, the attack rate was 3.6% (2/56, 95% CI 0.6%–13.4%), before masking 5.1% (2/39, 95% CI 0.9%–18.6%). Conclusions. The risk of wild-type SARS-CoV-2 transmission during air travel seemed low, but not negligible. In order to formulate an effective, evidence-based NPI protocol for air travel, further studies considering the different transmissibility of SARS-CoV-2 variants of concern and vaccination status are needed.